Understanding Costumer Intention in Using Online Ticket Purchasing as Self-Service Technology - Fahmi Ardhi (Prosiding Industrial Research Workshop and National Seminar, 2018)
This study present and modifies the technology acceptance model (TAM) in understanding behavioural intentionto use for online ticket purchasing. With 306 respondent, this study identifies the relationship and influence amongperceived ease of use, technology readiness, perceived usefulness, attitude towards using, and behaviouralintention to use. The findings revealed that technology readiness is the determinant factor in forming an attitudetowards using and perceived usefulness on the contrary. These findings can be used for Cinema company to attractmore people using online ticket purchasing since its still lack of user although this technology exists for customerbenefit.